BAGI HASIL KERJASAMA AKAD MUKHABARAH MENURUT FIQIH ISLAM DAN UU NO. 2 TAHUN 1960 DI DESA MANGUNSARI - Syamsuri Syamsuri; Muchamad Zainur Rohman (Al-Maslahah : Jurnal Ilmu Syariah, 2022)
Mangunsari Village is a village that has great agricultural potential because most of the village area is in the form of rice fields, and the majority of them work as farmers, the limited number of farmers who own their own land so that the background for the production sharing agreement on these rice fields. The profit sharing agreement that occurred in Mangunsari Village involved two parties, namely the land owner and the tenant, the contract used was based on ʻurf, namely verbally with a kinship element. This study aims to determine the agreement for the results of Mukhabarah in Mangunsari Village according to Islamic law and Law No. 2 of 1960, the method used is descriptive qualitative, data collection is carried out by interview, observation and documentation, collaboration with this profit sharing is in accordance with Islamic sharia, namely although the contract is not done in writing and there is no time limit and it is' Urf that has been used for a long time, but the profit sharing that has been carried out has not fully reflected justice with a percentage of 50:50 because all costs are borne by the cultivator. while according to Law no. 2 of 1960 the practice of cooperation was not fully in accordance with the main existing law in article 4 paragraph 1, article 3 paragraph 1 and the general explanation of paragraph 3 letter a.Keywords: Mukhabarah, 'Urf, Law no. 2 of 1960